1977
DOI: 10.1017/s0021859600034973
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil type and related factors on sugar beet yield

Abstract: Yields of sugar and responses to fertilizers were determined in about 400 fertilizer experiments on farms throughout the sugar-beet growing areas of Britain during 14 years from 1957 to 1970. The soil at each experimental site was described and classified and the records of the experiments have been examined to determine which properties of the soil influence sugar yield. The effect of year, rainfall, elevation, region and other factors such as sowing and harvesting date were also investigated.Year-to-year var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The increases in dry matter yield in the current study may be partially attributed to recent advances in sugar beet breeding (Loel et al, 2014;Hoffmann and Kenter, 2018) and changes in agronomic practices (Scott and Jaggard, 2000;El-Geddawy et al, 2008;Curcic et al, 2018). Location differences, including soil type (Goodman 1968;Webster et al, 1977) and temperature regime (Milford et al, 1980;Milford et al, 1985;Tsialtas and Maslaris, 2014) may also contribute to yield differences between the two studies.…”
Section: Amount and Rate Of Dry Matter Accumulationmentioning
confidence: 67%
“…The increases in dry matter yield in the current study may be partially attributed to recent advances in sugar beet breeding (Loel et al, 2014;Hoffmann and Kenter, 2018) and changes in agronomic practices (Scott and Jaggard, 2000;El-Geddawy et al, 2008;Curcic et al, 2018). Location differences, including soil type (Goodman 1968;Webster et al, 1977) and temperature regime (Milford et al, 1980;Milford et al, 1985;Tsialtas and Maslaris, 2014) may also contribute to yield differences between the two studies.…”
Section: Amount and Rate Of Dry Matter Accumulationmentioning
confidence: 67%
“…The response of sugar beet to fertilizer nitrogen and soil mineral nitrogen was also higher on sandy soils, although to a much lesser extent than in the case of pota toes. Draycott & Durrant (1973) and Webster et al (1977) also found that sugar beet required more nitrogen on sandy soils than on heavier soils. Nitrogen losses as a result of the higher risk of leaching are probably responsible for the somewhat stronger response on sands.…”
Section: Soil Typementioning
confidence: 94%
“…The most widespread classification systems, USDA Soil Taxonomy and the World Reference Base for Soil Resources (WRB) (ROSSITER et al, 2017;ESFANDIARPOUR et al, 2018;SALEHI, 2018) were compared according to parent material (SOROKIN et al, 2021), classification levels, physical and chemical properties, and other features by many researchers. SHRADER et al (1960) WEBSTER et al (1977, ALLGOOD & GRAY (1978), OGUNKULE & BECKETT (1988), BUOL et al (2011 studied the utility of soil classification systems for predicting selected properties and productivity, and our work follows this tradition.…”
Section: Introductionmentioning
confidence: 98%